Evaluation of the NINCDS-ADRDA criteria in the differentiation of Alzheimer's disease and frontotemporal dementia. Issue 2 (1st February 1999) - Varma, A R; Snowden, J S; Lloyd, J J; Talbot, P R; Mann, D M A; Neary, D
Abstract : OBJECTIVES: The diagnosis of Alzheimer's disease (AD) is now reliant on the use of NINCDS-ADRDA criteria. Other diseases causing dementia are being increasingly recognised—for example, frontotemporal dementia (FTD). Historically, these disorders have not been clearly demarcated from AD. This study assesses the capability of the NINCDS-ADRDA criteria to accurately distinguish AD from FTD in a series of pathologically proved cases. METHODS: The case records of 56 patients (30 with AD, 26 with FTD) who had undergone neuropsychological evaluation, brain imaging, and ultimately postmortem, were assessed in terms of whether at initial diagnosis the NINCDS-ADRDA criteria were successful in diagnosing those patients who had AD and excluding those who did not. RESULTS: (1) The overall sensitivity of the NINCDS-ADRDA criteria in diagnosing "probable" AD from 56 patients with cortical dementia (AD and FTD) was 0.93. However, the specificity was only 0.23; most patients with FTD also fulfilled NINCDS-ADRDA criteria for AD. (2) Cognitive deficits in the realms of orientation and praxis significantly increased the odds of a patient having AD compared with FTD, whereas deficits in problem solving significantly decreased the odds. Neuropsychological impairments in the domains of attention, language, perception, and memory as defined in the NINCDS-ADRDA statement did not contribute to the clinical differentiation of AD and FTD. CONCLUSION: NINCDS-ADRDA criteria fail accurately to differentiate AD from FTD. Suggestions to improve the diagnostic specificity of the current criteria are made.